STRATEGI GURU DALAM MENINGKATKAN KUALITAS BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA ISLAM SINGOSARI - Rizki Ambarini; Maskuri Maskuri; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The use of teacher strategies, especially in Islamic religious education subjects at Muqorrobin Singosari Islamic Junior High School, has been running effectively and pleasantly for students. The fokus of the research discusses the planning, implementation and evaluation of teacher strategies in improving the quality of student learning in Islamic religious education subjects at SMP Islam Muqorrobin Singosari. To achieve this goal, the researcher uses a qualitative approach with the type of research that produces data from interviews and documentation in collecting data to provide an overview or form of presenting research reports. Researchers found research results from planning including the existence of a curriculum, learning implementation plans and learning media. Implementation includes preliminary activities, core activities using a scientific approach and closing activities. Evaluation includes evaluation of cognitive aspects, evaluation of affective aspects and evaluation of psychomotor aspects.